Pelatihan Pembuatan Pakan Fermentasi untuk Peningkatan Efisiensi Penggemukan Hewan Ternak - Tamrin; Syahril, Efendi; Fauzan, Nurahmadi (Cattleya Darmaya Fortuna, 2024)
This article explores a training initiative on fermented feed production to enhance livestock fattening efficiency in Kampung Kunyit, Rawa Keong, Deli Serdang. The program aims to economically empower local livestock farmers. Through hands-on training, participants acquire essential skills in designing and producing high-quality fermented feed for sheep or goats, thereby improving overall livestock fattening processes. This intervention aligns with the community's economic development goals, promoting sustainable practices in animal husbandry for enhanced livelihoods. The training focuses on fermented feed production to support highly efficient livestock fattening. Participants engage in practical sessions, gaining crucial skills in designing and producing high-quality fermented feed. It is anticipated that livestock farmers in Kampung Kunyit can enhance their economic well-being through sustainable farming practices. The implementation of fermented feed is expected to enhance nutrient absorption by livestock, expedite fattening processes, and reduce feed costs. Consequently, this article not only provides practical guidance in feed production but also contributes to improving farming efficiency, supporting local economic empowerment efforts. The results of this training are expected to stimulate positive changes in the community's farming approach, leading to increased productivity and income. Therefore, the implementation of fermented feed production practices is envisioned as a tangible step toward sustainable economic resilience in Kampung Kunyit, Rawa Keong, Deli Serdang. This article offers a substantial contribution to local economic empowerment through innovative livestock feed management and has the potential to serve as a guide for similar communities in achieving economic sustainability in the agricultural sector.